Crystallographic orientation dependent fracture behavior in tantalum single crystals. (15th January 2021) - Lim, Hojun; Noell, Philip J.; Carroll, Jay D.
Abstract: We report crystallographic orientation dependent fracture behavior in tantalum single crystals with the tensile axes oriented close to [100], [110] and [111] directions. Three tantalum single crystals were deformed in quasi-static, uniaxial tension and their fracture surfaces were characterized. To understand different deformation modes and failure mechanisms, crystal plasticity-finite element (CP-FE) simulations were performed. Both experiments and CP-FE simulations showed strong strain localization and shear banding in the ~[100] specimen, little rotation and profuse necking in the ~[110] specimen, and significant crystal rotations associated with shear-dominated behavior in the ~[111] single crystal. In addition, voids were observed in fracture surfaces of ~[100] and ~[111] single crystals while the ~[110] specimen was void-free. The failure processes of these single crystals showed that dislocation boundaries are necessary for void nucleation in pure tantalum. This work demonstrates strong effects of crystallographic orientations in failure behaviors. Graphical Abstract: Image, graphical abstract